2017
DOI: 10.1017/s146625231700010x
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacillus pleuropneumoniae biofilms: Role in pathogenicity and potential impact for vaccination development

Abstract: Actinobacillus pleuropneumoniae is a Gram-negative bacterium that belongs to the family Pasteurellaceae. It is the causative agent of porcine pleuropneumonia, a highly contagious respiratory disease that is responsible for major economic losses in the global pork industry. The disease may present itself as a chronic or an acute infection characterized by severe pathology, including hemorrhage, fibrinous and necrotic lung lesions, and, in the worst cases, rapid death. A. pleuropneumoniae is transmitted via aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 128 publications
0
30
0
Order By: Relevance
“…The indirect route of transmission via surface was not considered very important and therefore the ability of A. pleuropneumoniae to survive in the environment outside of its host is not yet known ( 25 ). Previous studies from our group demonstrated that A. pleuropneumoniae is able to grow in unsuitable environments when forming multi-species biofilms with other respiratory pathogens of pigs that are also part of the porcine respiratory disease complex ( 6 , 17 , 27 ). In this study, a total of 10 samples of drinking water were taken from a swine farm in the State of Aguascalientes where previously Loera-Muro et al ( 26 ) detected the presence of A. pleuropneumoniae in drinking water using a specific PCR for apxIV gene.…”
Section: Discussionmentioning
confidence: 99%
“…The indirect route of transmission via surface was not considered very important and therefore the ability of A. pleuropneumoniae to survive in the environment outside of its host is not yet known ( 25 ). Previous studies from our group demonstrated that A. pleuropneumoniae is able to grow in unsuitable environments when forming multi-species biofilms with other respiratory pathogens of pigs that are also part of the porcine respiratory disease complex ( 6 , 17 , 27 ). In this study, a total of 10 samples of drinking water were taken from a swine farm in the State of Aguascalientes where previously Loera-Muro et al ( 26 ) detected the presence of A. pleuropneumoniae in drinking water using a specific PCR for apxIV gene.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation is reportedly involved in escaping from the host immune system, thereby playing an important role in the pathogenicity of A. pleuropneumoniae in vivo (Bosse et al, 2010 ; Hathroubi et al, 2017 ). The predominant sign of acute pleuropneumonia is high fever that body temperature can elevated up to 41.8°C (Menzel et al, 2014 ; Sassu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible to use these approaches outside the common model organisms to study complex phenotypes such as biofilm formation. Shifts in gene expression have been specifically associated with the biofilm lifestyle, across many different bacteria, and in different biofilm contexts [3,[7][8][9]. A wide distribution of gene-expression patterns have been observed, and there is a great deal of variability that is both strain specific and driven by experimental setup.…”
Section: Introductionmentioning
confidence: 99%